The numerical estimation method of series FACTS compensator based on injection model of voltage source inverter - Shahariari, A.; Mokhlis, Hazlie; Bin Abu Bakar, A.H.; Karimi, M. (IEEE, 2011)
This paper presents new numerical injection model of Inter Line Power Flow Controller (IPFC). Indeed, linear model of voltage source inverter of IPFC is improved to estimate steadystate operation of IPFC as well as Static Synchronous Series compensator (SSSC) in power system. The proposed method estimates the effect of IPFC on active and reactive line power flow with SSSC for three modes such as resistive, capacitive and inductive. Thus, it is recommended that the proposed technique can be applied for prediction of initial injected voltage and its phase angle of IPFC and SSSC for their modeling in real system. The tested system for simulation is based on IEEE two machine systems. The result of simulation and the numerical analysis shows the robust accuracy of obtained estimation of IPFC and SSSC.